Weed Community Structure in Patia Village Rice Fields Patia Sub-District, Pandeglang Regency - Ai Widiyawati; Hadi Susilo; Mu'jijah Mu'jijah; Suyamto Suyamto; Nurullah Asep Abdilah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Rice is a very important type of food crop because it is a staple food source. Crop losses at the farmer level due to competition with weeds reach 10-1.5%. This study aims to determine the structure of rice weed communities in rice fields in Patia Village, Patia District, and Pandeglang Regency. The research method uses an observation method with the sampling technique used as a random method. The plot used was 2 m x 2 m. Weed sampling was carried out by recording the types of weed types and counting the number of individuals of each species. Measurements of environmental factors such as temperature, humidity, pH, and light intensity were measured. The data parameters measured include the Shannon-Wiener diversity index (H'), evenness index (J'), dominance index (D), wealth index (S), and abundance of rice weed species. The results of the study were that the types of rice weeds found in the rice fields of Patia Village, District, and Patia, Pandeglang Regency, namely Ludwigia octovalvis (Jacq) Raven, Commanded cylindricaL. Beauv, Spigelia anthelmia, Ageratum conyzoides, Spihemoclea zeylanica, Altemanthera sessillis, Eclipta prostate, Cypress deformed L., Digitaria sp. and Mimosa chaste L. The structure of the weed community in the rice fields of Patia Village, Patia District, Pandeglang Regency is the Shannon-Wiener Diversity Index (H') of 1.94; Evenness Index (J') of 0.884; Dominance Index (D) of 0.15.